Noncompaction Cardiomyopathy with Charcot-Marie-Tooth Disease - Sherif Ali Eltawansy; Andrea Bakos; John Checton (Case Reports in Cardiology)
We report a case of a 53-year-old female presenting with a new-onset heart failure that was contributed secondary to noncompaction cardiomyopathy. The diagnosis was made by echocardiogram and confirmed by cardiac MRI. Noncompaction cardiomyopathy (also known as ventricular hypertrabeculation) is a newly discovered disease. It is considered to be congenital (genetic) cardiomyopathy. It is usually associated with genetic disorders and that could explain the genetic pathogenesis of the non-compaction cardiomyopathy. Our case had a history of Charcot-Marie-Tooth disease. There is a high incidence of arrhythmia and embolic complications. The treatment usually consists of the medical management, defibrillator placement, and lifelong anticoagulation. Heart transplantation will be the last resort.